2013
DOI: 10.5171/2013.383486
|View full text |Cite
|
Sign up to set email alerts
|

A New Classification of Zygomatic Fracture Featuring Zygomaticofrontal Suture: Injury Mechanism and a Guide to Treatment

Abstract: The researchers establish a new classification system for zygomatic fractures based on computed tomography and mechanism of injury, which could be used to inform treatment options.Patients treated for isolated zygomatic fracture at the Keio University Hospital between 2004 and 2011 were recruited for this study. The cases were classified into 4 types based on the fracture pattern of the zygomaticofrontal suture and inferior orbital rim.In total, 113 patients aged 16 to 82 years (mean age (SD) = 39.8 (17.0) yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…We observed that there were 65 (65.0%) male and 35 (35.0%) female patients with a male to female ratio of 1.9:1. The findings of our study are in line with the study done by Noor et [14,15].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observed that there were 65 (65.0%) male and 35 (35.0%) female patients with a male to female ratio of 1.9:1. The findings of our study are in line with the study done by Noor et [14,15].…”
Section: Discussionsupporting
confidence: 93%
“…A higher proportion of 31-45 years age group has also been reported by Balakrishnan et al (2015) who observed that 61.3% of such patients in India were aged between 31-45 years [13]. Zhang et al (2018) reported comparable mean age of 33.6±11.4 years in Chinese such patients [14] while Ogata et al (2013) reported it to be 39.8±17.0 years in Japan [15]. Salinas et al (2013) observed it to be 40.3±7.9 years in such patients in USA [16].…”
Section: Discussionsupporting
confidence: 50%
“…This study also supports other study conducted in gender based population showing male being more affected. 7,20 This may be because of male involved in physical activities, traveling and also practice drink and drive. Previous studies show left side is predominantly affected in facial trauma which also favours our study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show left side is predominantly affected in facial trauma which also favours our study. 19,20 This predominance of the side might be because most people are right hand and try to protect themselves from injury using their dominant hand. Also in the physical assault there will be more blows in the same direction of the opponent strong arm.…”
Section: Discussionmentioning
confidence: 99%
“…2 The zygomatic bone fractures are the one of the most common mid-facial bone fracture. 3 The commonest causes of ZMC fractures are RTAs, falls, violence, work and sports accidents, gunshot wound/blast injuries. Incidence of these fractures is more common among males than females with a 3-5:1 whereas in underdeveloped countries the ratio is as high as 10-40:12.…”
mentioning
confidence: 99%